Chronology and results of the fight against corruption in the judicial system of Ukraine - Рощина, Інна Олександрівна; Багрійчук, Дмитро В’ячеславович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Today, all citizens enjoy and understand that the judicial system of Ukraine is actually a brake on the further development of democracy, and in a corrupt state, as is well known, the most flagrant and open violation of the rights and freedoms of citizens. The level of corruption in Ukraine is not only high compared with other States, but continuously growing. Did not just say all the presidents of Ukraine and even adopted laws and programmes to combat corruption. Therefore, the author will review all regulations that were adopted to combat corruption in General, and then that were aimed at combating corruption in the judicial system. Summing up the results of the fight against corruption on the basis of regulatory acts issued during the time of independence of Ukraine, the author concludes that despite recent and ongoing efforts aimed at fighting corruption, Ukraine has become one of the corrupt country in the world, and the extent of corruption in the state not only do not decrease but rather increase. In other words, the more planned and conducted various activities to combat corruption, the faster it spreads in society. In the endless lamentations of the authorities, throughout the independence period of the country, about corruption in the state, is clearly seen as an explicit part of the officials in this corrupt system. And if so, then there is no real fight against corruption in Ukraine has not been, and is unlikely in the near future, without the adoption of the indigenous and radical measures. And above all here we need the political will of the leadership of the country, but it is not yet in sight.